RECOVERY OF LIQUID WASTE FROM A CURTIEMBRE STAGE UNHAIRING - Salas C., Gilberto (2006)
An experimental study on precipitation and recovery of dissolved proteins in wastewater from a tannery, which is achieved is when its isoelectric point is reached pH between 4.6 to 5.5 using acid solutions in the present work sulfuric (H2SO4). The recovery of the protein is above 80% and the reduction of BOD in the effluent is greater than 50%.